Constitution of Anodizing Current and Effects on the Growth of Porous Anodic Alumina. Issue 6 (1st January 2017) - Wang, Li-ping; Li, Geng; Liu, Xiao-han; Xia, Si-yuan; Jia, Hong-bing
Abstract : Field-assisted dissolution theory was the generally accepted mechanism for pore formation and development in porous anodic aluminum oxide (AAO). However, field-assisted dissolution rate or dissolution current has never been reported. The quantitative relationship between the length of AAO and total anodizing current J total is unclear, because the constitution of J total is hard to be determined in situ. In order to make clear of the constitution of J total and effects on AAO growth, different anodizing processes in two electrolytes (0.3 M and 0.7 M H2 C2 O4 ) are explored under constant current rather than constant voltage. Quantitative relationship between AAO lengths (y) and total anodizing currents (x) were investigated. Two fitting equations in 0.3 M and 0.7 M H2 C2 O4 are y = 0.92(x−4.58) and y = 1.00(x−5.05), respectively. The interesting results indicate that the J total is composed of ionic current J ion and electronic current J e, the pore development and the length of AAO are attributed to the J ion rather than the dissolution current, the corresponding J e = 4.58 and 5.05 mA/cm² contribute to the formation of oxygen bubbles which act as models for the pore formation in 0.3 M and 0.7 M H2 C2 O4, respectively. This is an efficient and simple method to determine the kinetics of porous anodic oxides.